Sistem Pembinaan Luar Lembaga Bagi Narapidana Yang Merata Dan Berkeadilan Berperspektif Pada Tujuan Pemasyarakatan - Wardhani, Noeke Sri; Hartati, Sri; Rahmasari, Helda Rahmasari (Jurnal Hukum & Pembangunan, 2015)
The purpose of the first year research is to explain the implementation of Pembebasan Bersyarat (PB), Cuti Menjelang Bebas (CMB) and Cuti Bersyarat (CB) to indentify the obstacles of the implementation and to arrange the model concept of outside institution development for the prisoners in regard to the implementation of PB, CMB and CB that is fair, equitable and based on the perspective of correctional purpose. In the second year, the purpose of the researh is to carry out workshop in regards to socialized the model concept of outside institution development for the prisoners in regard to the implementation of PB, CMB and CB, that is fair, equitable and based on the perspective of correctional purpose. The result of the first year research will be cross-checked with the response paper from the Regional Office of Ministry of Law and Human Rights in Bengkulu, Correctional Institution in Bengkulu (Lembaga Pemasyarakatan Bengkulu and Balai Pemasyarakatan (Bapas) Bengkulu. Based on the workshop, we will give input to the Directorate General of Correctional System at the Ministry of Law and Human Rights (Dirjen Pemasyarakatan) to make the policy of outside institution development. This research is a descriptive-explanatory research and use Sociology of Law as its approach. The data was be collected by questionnaire, in-depth interview, observation and literature study which identifies Penelitian Kemasyarakatan (Litmas) and the document of PB, CMB and CB which will be determine purposively. The primary data was collected by interviewing the staffs and the officials of the relevant authorities regarding the implementation of PB, CMB and CB. The primary data was collected from the prisoners and their family, whether they apply for the PB, CMB or CB or not. The data analysis was carried out continuously from the beginning to the end of the research by doing data triangulation, through assessment, categorization, evaluation, comparison and synthesis. The result of the research: First, the implementation process of PB, CMB and CB to the prisoners is already carried out Tim Pengamat Pemasyarakatan (TPP) Correctional Institution in Bengkulu, Pembimbing Kemasyarakatan (PK) Balai Pemasyarakatan (Bapas) Bengkulu and TPP Regional Office of Ministry of Law and Human Rights in Bengkulu. However, the implementation process is not quite fair and equitable since not all of the prisoners can apply for PB, CMB or CB because they do not have enough money and guarantor.There is a certain amount of money that needs to be paid by the prisoners as the documentation fee, although there is an anti-halinar program which prohibits fee collection. In June 2013, there was a program, called crash program, which helped the prisoners who do not have money and guarantor to apply for PB, CMB or CB, but only a few of them got the benefit of this program. Second, the are obstacles in the implementation of PB, CMB and CB. In their implementation from 2012 to 2013, some of the obstacles are regarding administrative issues. The research team proposes for the distinction between the model concept of PB, CMB and CB for the special crime prisoners and general crime prisoners. The research team proposes that the fair and equitable PB, CMB and CB, in the form of crash program, should be given free of charge to the general crime prisoners, and for the special crime prisoners should pay certain amount of fee as determined by the authority.